Transgenic rabbits expressing human lipoprotein lipase - Araki, Masahiro (Kluwer Academic Publishers, 2000)
To study the functions of lipoprotein lipase (LPL) in lipid and lipoprotein metabolism and the relationship between LPL and atherosclerosis, we generated transgenic rabbits expressing the human LPL gene. A total of 4045 Japanese whiterabbit embryos were microinjected with a 3.8-kb SalI/HindIII fragment containing the chicken β-actin promoter, human LPL cDNA and rabbit β-globin with poly (A) signals, and then transplanted into 116 recipient rabbits. Of the 166 pups born, six pups were transgenic as confirmed by Southern blot analysis. ANorthern blot analysis revealed that human LPL was expressed by a number of tissues including the heart, kidney, adrenal gland and intestine. One transgenic rabbit showed up to 3-foldincreased LPL activity in post-heparin plasma compared to thatin nontransgenic rabbits. Human LPL expression in various tissues of transgenic rabbits was further elucidated by in situ hybridization and immunostaining. Since rabbits are superior to mice as a model of atherosclerosis, this transgenicrabbit model should provide a valuable tool for the study of LPL in lipid metabolism and atherosclerosis.